Challenging the status quo of sustainability : permaculture fostering human-nature relations and re-enchanting nature in Uppsala - Syed, Owais (SLU/Dept. of Urban and Rural Development, 2022)
To understand the current situation when it comes to the environmental challenges humans and nature are facing in 21st century, I think there is a need to look back in history to search for root causes. In order to understand how historically, views of nature and human-nature relationships emerged impacting our current age, e.g., how enlightenment and modernity led to a dis-enchantment of nature. The thesis also explores current views of nature, to see if there are any connection between these. The aim of this thesis is to gain a deeper understanding if permaculture might contribute to a change in view of nature, through studying a permaculture movement called Ultuna permaculture in Uppsala, Sweden. The group consists of students and is active in an area called Ultuna, where one of Swedish University of Agriculture Science main campus is located. The views of nature will be explored through observations and interviews with the board members of Ultuna permaculture and paid extra attention to if and how they have been impacted by their engagement with permaculture. These views in turn influence how humans relate to nature and approach her, and how their view of nature impacts their view on sustainability. Findings show that for some members, whom already have a relationship to nature due to much time spent in nature or being on a quest to address issues of climate change, permaculture becomes a way to practically do something about it. To work towards something that in common day term is known as ‘sustainability’ or ‘sustainable developmentâ€™, these terms are not viewed as something positive in the movement or defined in term of permaculture. There are also views of spirituality, and nature being something more than the observable, reminding of the idea of enchantment. Concluding that permaculture is re-enchanting nature in Uppsala, beyond the notion of sustainability.